Introduction of Android Based Vibration Measurement When Transporting Water Apple Camplong - Iswahyudi, Iswahyudi; Darmawati, Emmy (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
The camplong water apple (Syzygium aqueum (Burm.f.) Alston) is a superior fruit of Madura which has economic value. It is needed in fresh form but is easily damaged. Product freshness will be maintained if proper packaging and transportation are carried out. The purpose of this research was to carry out actual transportation of guava water and introduced a new way of measuring vibrations based on Android. The scale for measuring vibrations in the field was based on MMI (Modified Mercalli Intensity Scale). The results showed that the measurement of vibration using Android directly illustrated the effect of vibration during transportation on packaging, the vibration generated was 7-8 MMI and the resulting force was 0.8 - 1.2 kgf so that it did not affect the packaging used. The percentage of mechanical damage to guava air camplong after transportation was 20.87% on farmer packaging and 7.70% on RSC packaging.